Educação e cidadania na pós-modernidade - Veríssimo, Mara Rúbia Alves Marques (1996)
Considering the recurrent reference to the formation of citizenship as a presumptive objective of educational policies and practices, the present work consisted of a process of pedagogical self-criticism that aimed to understand the relationship between education and citizenship in the Postmodemity context, with a view to understanding the meaning of educating for citizenship today. For this, we criticized the modern liberal bases of the concept of citizen, which associated more knowledge / reason to progress and social transformation, placing school education at the center of social life, as a rationalist cultural locus, dissociated from the social world, by an interpretation. meaning of citizenship. We start from the assumption that citizenship is defined not by rational content as a product of the socialization of universally valid knowledge, but by the historical process of struggles for existential qualification through social practices and movements, that is, the subject is conceived as social movement. Methodologically, we first analyzed citizenship in the light of Postmodemity's historical-societal conformations, during which time citizenship was being expressed through the latest emancipatory and / or contesting social movements at the level of civil society. In a second moment, we consider critically the pillars of modern thought in function of its interpretations about the relations between the historical conditions and the knowledge itself and its influences in the main modern pedagogical theories that have marked the current practices and policies in education. In a third moment we recover some postmodern theoretical assumptions concerning the societal conditions of Postmodernity, in order to identify elements of a postmodem critical theory that can underpin educational discourses about citizenship. We conclude that citizenship is a fundamental epistemic category in school education because it allows the perception of collective and individual cultural experiences linked to a global democratic pattern of social relations, enables an inversion of the conceptions about Modernity as a space of struggles and social contradictions and, for this reason. Finally, beyond the dominant formal knowledge, it considers the dimensions of other knowledge as cultural and symbolic productions, incorporating new languages ​​and patterns of rationality corresponding to the plurality of social practices. In this sense, the reconstruction of the concept of citizenship in the educational field proved to be important as a category that articulates the constitutive dimensions of the socio-historical praxis - the epistemological, the historical-societal and the pedagogical - that synthesize the relations of the subjects or subjectivities with the subject. knowledge, the social and the education.